Removal of sediment through hydro-suction revisited: An extensive review of the hydro-suctioning method, widely used for sediment removal from the water bodies - Akash Jaiswal; Z. Ahmad; S. K. Mishra (Water Practice and Technology, 2022)
Hydro-suctioning is used to remove the deposited sediment from water bodies. A suction pipe is placed on/above/below the sediment bed, and deposited sediment is removed using suction. The sediment movement during hydro-suction, flow pattern, temporal sediment concentration, and scour profile are reviewed extensively and summarized in this paper. It is seen that the sediment removal initiates due to lift forces and continues further due to a change in flow field that creates sediment resuspension. The sediment removal ceases if the suction inlet reaches a distance, i.e., critical suction inlet depth. Within this critical zone, when the hydro-suction initiates, sediment just below the suction pipe is first removed, leading to the maximum scour depth, i.e., below the sediment bed level. In this process, sediment from sides of the scour hole is hydrodynamically dragged towards the center, where it gets deposited, and a hump is formed at the center. At equilibrium, the sediment removal ceases. This paper discusses the equations predicting scour profile and critical inlet depth. It is seen that the research work dealing with the standardization of hydro-suction for fixation of suction pipe diameter, suction inlet depth, discharge, etc. is in quite a primitive stage and needs urgent attention. HIGHLIGHTS Sedimentation in water bodies.; Sediment removal through hydro-suction.; Flow pattern near the mouth of the suction pipe.; Formation of scour profile due to hydro-suction.; Temporal variation of sediment concentration in the suction pipe.;